Structural econometrics essays in methodology and applications in memory of Sanghamitra Das - Das, Sanghamitra; Dutta, Bhaskar (New Delhi Oxford University Press, 2010)
In memory of Sanghamitra Das, 1958-2008, Indian economist; contributed articles; most previously published.
Includes bibliographical references.
Keywords: Econometrics; Cement industries -- United States -- Mathematical models; Computer industry -- India -- Mathematical models